The Sting of Social: How Emphasizing Social Consequences in Warning Messages Influences Perceptions of Risk. (March 2017) - Murdock, Mitchel R.; Rajagopal, Priyali
This research examines the effects of warning messages that emphasize the social consequences of negative health outcomes. The authors demonstrate that highlighting social (vs. health) consequences leads to greater perceived temporal proximity of and increased perceived vulnerability to the outcome, thereby affecting risk perceptions, behavioral intentions, and customer perceptions of actual experience. They document this effect across five studies in different health domains including flossing (Study 1), soda consumption (Study 2), smoking (Study 3), and unprotected ultraviolet light exposure (Studies 4 and 5). These findings point to the important role of the consequence type highlighted in warning messages, which can have a significant impact on risk perceptions and consumer experiences.